Differential Technique of Training on the Basis of Diagnostics of Students’ Learning Capabilities (Journal of Advanced Research in Social Sciences, 2019)
An author’s differential technique of training has been developed, which presupposes the identification of individual typological differences of students (learning capabilities) and the development on this basis of strategies for organizing interaction between the teacher and the learner (student). The differential technique includes the following components: invariant (heuristic algorithmic prescription) and variable (learning strategies for five typological groups of students). The effective implementation of the differential technology is provided by a set of diagnostic training facilities with computer support, aimed at training the teacher and at ensuring the learning process.